2008
DOI: 10.1557/jmr.2008.0329
|View full text |Cite
|
Sign up to set email alerts
|

Laser deposition of a Cu-based metallic glass powder on a Zr-based glass substrate

Abstract: Laser Engineered Net Shaping (LENS™) is a laser-assisted manufacturing process that offers the possibility of producing metallic coatings and components with highly nonequilibrium microstructures. In this work, the microstructure developed by LENS deposition of Cu 47 Ti 33 Zr 11 Ni 8 Si 1 powder on a bulk metallic glass substrate, with nominal composition Zr 58.5 Nb 2.8 Cu 15.6 Ni 12.8 Al 10.3 , is investigated. Single-layer deposition results in the formation of an inhomogeneous but partially amorphous layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 47 publications
(47 reference statements)
5
29
0
1
Order By: Relevance
“…Prior work on metallic glasses has shown that the depth of the melt zone and the thickness of the HAZ both increase with increasing heat input. [12] The effect on the morphology of the HAZ is also observed in the present study, where increasing the laser travel speed, and thereby reducing the heat input, nearly eliminates the formation of a crystalline HAZ in the amorphous substrate (Figure 1(c)). Indeed, a combination of laser power at 150 W and travel speed at 21.2 mm/s, or a heat input of 7.1 J/mm 2 , appears to be close to ideal for successfully forming a melt pool, necessary for powder incorporation, without causing extensive crystallization in the underlying amorphous substrate.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Prior work on metallic glasses has shown that the depth of the melt zone and the thickness of the HAZ both increase with increasing heat input. [12] The effect on the morphology of the HAZ is also observed in the present study, where increasing the laser travel speed, and thereby reducing the heat input, nearly eliminates the formation of a crystalline HAZ in the amorphous substrate (Figure 1(c)). Indeed, a combination of laser power at 150 W and travel speed at 21.2 mm/s, or a heat input of 7.1 J/mm 2 , appears to be close to ideal for successfully forming a melt pool, necessary for powder incorporation, without causing extensive crystallization in the underlying amorphous substrate.…”
Section: Discussionsupporting
confidence: 81%
“…Although the local cooling rate was not measured directly in the present work, finite element method (FEM) simulations of a moving heat source analogous to the laser heating process indicate that the maximum cooling rate of the center of the melt zone is approximately 8000 to 10,000 K/s. [12,15] This is orders of magnitude higher than the critical cooling rate required to avoid crystallization of the Zr-based BMG (~1.75 K/s [16] ) used in the present study. Moreover, the DSC data presented in Figure 5 reveal slightly higher glass transition temperatures in the deposited material than the as-cast glass.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Bulk metallic glasses (BMGs) with both glassy-state structure and metallic-bonding character show a series of intriguing mechanical, physical, and chemical properties, having wide range functional and structural applications. [8][9][10][11][12] Due to rapid heating and cooling, lasers have been widely used to welding, cutting, cladding, alloying, glazing, annealing, melting, or ablating the small-scaled amorphous alloys such as ribbons, films, and wires, [13][14][15][16][17] very recently extending to BMGs. 18,19 Through laser-processing, microstructures, 15-17 magnetic properties, 14 forming ability, 20 and mechanical properties 19 of this kind of glassy alloys can be significantly improved, whereas only few works have focused on the surface patterns.…”
mentioning
confidence: 99%